The Method of Moral Education of Al-Khatib Al-Bagdadi (D.463 H) and Its Relevance to Islamic Education in Indonesia - Muh Ubaidillah Alghifary Slamet (Khazanah Pendidikan Islam, 2025)
This article examines the moral education method of Al-Khatîb Al-Baghdadî, a prominent hadith scholar from the 5th century Hijri, and assesses its relevance to contemporary Islamic education in Indonesia. This research uses a qualitative approach through literature review and content analysis of Al-Khatîb's two main works: al-Jami' and al-Faqîh wa al-Mutafaqqih. Technical data analysis through data reduction, display, and conclusion drawing. This study found that 1). the method of moral education of al-Khatîb al-Baghdâdî in his two works, namely Al-Jâmi' and Al-Faqîh found nine methods, namely the method of exemplary, habituation, advice, giving parables, stories / stories, lectures, asking questions, stimulation and threats, and the method of reward and punishment, and 2). These methods are still relevant to Islamic education in Indonesia, namely, these methods are still used and practiced, strengthen the science of Islamic education, can be developed and integrated with modern educational methods, emphasis on morals and the importance of manners, the application of morals in life, and the balance between the world and the hereafter.  The recommendations of this article offer actionable suggestions, including: the need to evaluate current Islamic teaching methods, improve educators' competence in delivering moral teaching, and encourage further research to assess the relevance and effectiveness of classical education models in the modern and digital era.